Exosomes in tuberculosis: Still terra incognita?. Issue 3 (14th October 2018) - Hadifar, Shima; Fateh, Abolfazl; Yousefi, Mohammad Hadi; Siadat, Seyed Davar; Vaziri, Farzam
Abstract: Today, diagnosis, vaccination, and treatment of tuberculosis (TB) remain major clinical challenges. Therefore, an introduction of new diagnostic measures and biomarkers is necessary to improve infection control. The ideal biomarker for TB infection can be defined as a host or pathogen‐derived biomolecule, which is potent for identifying infection and determining its clinical stage. Exosomes, defined as cell‐derived nanovesicles released into biological fluids, are involved in cell–cell communication and immune modulation. These vesicles have emerged as a new platform for improving the clinical diagnosis and prognosis of different infectious diseases and cancers. The role of these nanovehicles, as alternative biomarkers for the improvement of TB diagnosis and treatment, has been demonstrated in a significant body of literature. In this review, we summarized recent progress in the clinical application of exosome‐based biomarkers in TB infection. Abstract : Today, diagnosis, vaccination, and treatment of tuberculosis (TB) remain major clinical challenges. Therefore, an introduction of new diagnostic measures and biomarkers is necessary to improve infection control. Exosome‐based biomarkers for diagnostic and therapeutic purposes or vaccine development can be promising.